Terrorism & counterterrorism: a comprehensive introduction to actors and actions - Prunckun, Henry W. (Lynne Rienner Publishers, 2019)
What is terrorism? How do terrorists operate—what are their means, targets, and motivations? How can governments prevent terrorist attacks from happening? Henry Prunckun and Troy Whitford address these questions in their systematic, comprehensive exploration of terrorism and counterterrorism.